Sequence Inversion to Facilitate Concurrent Radiotherapy and Systemic Therapy. A Proof of Principle Study in the Setting of a Phase II Randomized Trial in Prostate Cancer - Wilke, Derek; Wood, Lori; Cwajna, Slawa; Rutledge, Robert; Hollenhorst, Helmut; Bowes, David; Patil, Nikhilesh; Ago, Casely T.; Pignol, Jean-Philippe (Frontiers in Oncology, 2020)
Background – Concomitant chemo-radiation for pelvic cancers remains challenging to be delivered at full doses. We hypothesized that fewer delays in chemotherapy would occur if the sequence of radiotherapy would be reversed, starting with the boost volume followed by the elective nodal volume. We report the result of a Phase II randomized study for high risk prostate cancer. Patients and method – The study was a double-blinded phase II randomized trial. Patients were eligible if they had non metastatic high-risk prostate cancer. All patients received 2.5 years of hormonal therapy and 46.5 Gy in 25 fractions to the pelvic lymph nodes. Patients received a radiation boost to the prostate, either before or after whole pelvic irradiation. Concurrent (20 mg/m2) docetaxel was given on the first day of radiotherapy and weekly thereafter for a total of eight treatments until predefined toxicity stopping rules. Results – 90 patients were included and randomized. Four were ineligible for the analysis. In total, 42 patients were randomized to the standard sequence, 44 patients to the experimental sequence. There were statistically fewer GI or GU toxicities leading to a docetaxel dose reduction or omission in the experimental sequence compared to the standard sequence, 5 versus 15 events (p = 0.027). There was no difference in overall survival, cause-specific survival or biochemical-relapse free survival between the two sequences. Conclusions – This is the first study to test sequence inversion for pelvic radio-chemotherapy in a randomised double-blind trial. Less chemotherapy interruptions or dose reductions occurred by inverting the radiation sequence of the large field and the boost. The trial was registered with Clinicaltrials.gov: NCT00452556